Physiotherapeutic proceedings with patient after petrochanteric fracture - Babkiewicz, Damian; Szczypiór-Piasecka, Karina; Mińko, Alicja; Antczak, Krzysztof (Journal of Education, Health and Sport, 2021)
Introduction: The elderly are often affected by hip fractures. A trochanteric fracture is defined as when the fracture fissure is between the capsule and 3 cm below the lesser trochanter. The most common cause of these fractures is osteoporosis in the elderly. Treatment of a trochanteric fracture may be operative or conservative. The aim of this study was to define a plan of physiotherapeutic treatment in a patient after fixation of a trochanteric fracture with an intramedullary nail. Materials and methods: The work was written based on the medical history of a patient with a trochanteric fracture. The entire treatment procedure was carried out at the Department of Orthopedics, Traumatology and Oncology of the Musculoskeletal System, located at Unii Lubelskiej 1 in Szczecin. Results: Rehabilitation is an indispensable element in the treatment process of patients after a trochanteric fracture. It is implemented already from 1 day after the surgery in order to activate the patient as soon as possible. Such a procedure is to ensure faster activation of the patient and to avoid adverse changes resulting from too long immobilization. Conclusion: Rehabilitation is an indispensable element in the treatment of patients after a trochanteric fracture. Early patient activation reduces the risk of postoperative complications.